Pengaruh bahan ajar IPA tema kesehatan pencernaan kita bermuatan literasi saintifik dalam pendekatan saintifik terhadap kompetensi siswa kelas VIII SMPN 25 Padang - Yolly Sawitri; Asrizal Asrizal; Renol Afrizon (Universitas Negeri Padang, 2019)
In the 21st century literacy skills are needed. The government encourages the School Literacy Movement (GLS) to further improve student literacy. Science learning in the 2013 curriculum is carried out in an integrated and integrated scientific literacy way and has a context in the real world. The facts that occur in the field, the integration in the IPA textbooks is still low and literacy is only just literacy reading that has just been applied. The solution to this problem is to use the Natural Science Teaching Material on the theme of our digestive health with scientific literacy in the scientific approach to the competency of class VIII students of SMP 25 Padang. The type of research used was a quasi-experimental design with Posttest-Only Nonequivalent Control Group Design. The sampling technique uses purposive sampling and cluster random sampling. The instrument for collecting data consisted of written test sheets of knowledge competencies, observation sheets from attitude competencies and performance assessment sheets from skills competencies. Data from the study were analyzed by descriptive statistical analysis and a comparison of two averages. Based on the research that has been done obtained data for competency attitudes, knowledge and skills. The results of the attitude, knowledge and skills competency analysis show that the proposed hypothesis is accepted at a significant level of 0.05. The results of the analysis showed that the use of science teaching materials had a significant influence on the competency of attitudes, knowledge and skills of class VIII students of SMP 25 Padang at the 95% confidence level. This result is applied to students in a scientific approach.